(untitled) (Research, Society and Development, 2021)
External causes often result in hospitalizations and deaths. For this reason, this work aims to track the main causes ande the ages ande sex most affected by them. Epidemiological data will help professionals to prepare for the best care for these patients. According to the figures collected in DATASUS, the major cause of hospitalization and deathes in Brazil and in Assis are the falls, with a predominance of the elderly age group. Another cause that draws a lot of attention is that which includes transport acidentes, especially motorcycle acidentes involving the male sex. It is hoped that this study can help to raise awareness and adequate collection of epidemiological data about Brazil, its regions and Assis.